Pengaruh Membaca Al-Qur’an Terhadap Penurunan Tekanan Darah Pada Lansia Hipertensi Di UPT Pelayanan Sosial Lanjut Usia Binjai - Rizki, Muhammad; Siregar, Maulana; Handayani, Ahmad; Sutysna, Hendra (Buletin Farmatera, 2025)
Abstract: Reading the Qur'an is a form of dhikr and as a meditation in positive benefits for the body. Hypertension is a condition when blood pressure in tFaculty of Medicine he blood vessels increases chronically at 140/90 mmHg. The prevalence rate in Binjai City in 2016 was found to be 366 hypertension patients. Therapy to read the Qur'an harmoniously and carefully can improve biochemistry in the body that lowers blood pressure. This study aims to determine the effect of reading the Qur'an on reducing blood pressure in the elderly with hypertension at the Binjai Elderly Social Service Unit. This study uses a type of quantitative research with a quasi-experimental method  with a non-randommized pre test-post test control group design. Based on the results of the study, it was found that there was an average difference between the intervention and control groups, where the systolic mean was 143.25 and diastolic 88.37, while the systolic and diastolic mean of the control group were 150.43 and 94.75. This is because the verses of the Qur'an read by hypertensive patients can activate endorphins naturally, thereby increasing feelings of relaxation and lowering blood pressure. It was found that  the P value in the final systolic variable was 0.034 which means that there was a mean difference between the final systolic in the intervention group and the control group because P was 0.05, while the P value in the final diastolic variable was 0.001 which can be concluded that there is a significant mean difference between the final systolic of the intervention group and the control group because of P 0.05. Based on this study, it was found that the majority of hypertension is found in women and 60-74 years old. There was a difference in average blood pressure in the intervention and control groups.